Exploring Islamic views on the application of gene transfer in tissue engineering approach - Mohamad Sukri, Norhamiza; Abdul Rahman, Rozlin; Ahmad Radzi, Muhammad Aa'zamuddin; Md Nazir, Noorhidayah; Zulkifly, Ahmad Hafiz; Hashi, Abdurezak Abdulahi; Mohamad, Mohd Yusof; Sha'ban, Munirah (2014)
Gene transfer technology has introduced new hope for the treatment of hereditary or acquired diseases. Used together with tissue engineering principles, their synergistic approach holds great potential over current treatment modalities. However, some debatable issues over its use and ramifications such as insecure efficiency and controllability of the duration of the effects linked the technology with increasing ethical concern and religious disputes. Hence, this work aims to explore those issues from the Islamic perspectives. It is well-defined that the process of integrating Islamic perspectives into human knowledge requires deep awareness from both Islamic and modern philosophy of knowledge. However, we distance ourselves from providing an ultimate Islamic decree on gene transfer. Questionable outgrowths of the technology among those are, is it morally acceptable to genetically engineer or modify genes? Is it ethical to apply the therapies on humans? Seeking remedies through modern science and technology is encouraged in Islam, provided it is used for the improvement of health and to prevent or cure diseases. But what are the scopes and limitations of gene transfer? The distinction between “therapy” that aims to prevent or treat disease, and “enhancement” that aims to improve human traits, plays a key role in the discussions since it could lead to a disastrous result. What if scientists manipulate genes to genetically control traits in human offspring that are not health related e.g. to ensure good looks? Will everyone in society have access to the technology? Or will it be so expensive only the rich can afford it? Therefore, it is imperative to consider the safety and efficacy of the proposed study and the availability of alternatives to balance between benefit and risks of gene therapy. This effort perhaps could provide a platform on how to achieve a consensus that deals with the scientific reality, the Islamic moral and legal jurisprudence that surrounds the technology.